(untitled) (Sociología y tecnociencia, 2013)
This contribution aims to analyze Sub-Saharan women’s migration with a special focus on highly skilled women in order to create a framework to better understand the different factors shaping migration patterns, such as the push and pull factors, the increase of flows and the complexity associated with them. In recent years the number of female Sub-Saharan migrants has grown at a rate much higher than the global average. In fact, in 2010 alone the number of female African migrants was 47.2% (World Bank, 2012), showing an increase of 5.2% since the 1960’s when women constituted 42% of the total migration from Sub-Saharan Africa. The feminization of migration flows from Sub-Saharan Africa (SSA) in recent years has also witnessed a diversification of the flows. One specific segment on the rise is labor migration, specifically, highly skilled migration, especially for tertiary students and physicians and nurses. The study explores social geography and the geography of migration. The author considers two dimensions of analysis: women’s migration patterns from SSA (with a special focus on the impacts of the flows) and highly skilled migration from SSA.